The Future of Nonnative Teachers of English - Nining Ismiyani (Universitas Pahlawan Tuanku Tambusai, 2021)
This paper discusses nonnative teachers of English who are often claimed to be less competent and qualified compared to their native counterparts. The aim of this paper is to elaborate that the identity of the teachers of English shall no longer be problematic in a matter of English Language teaching profession. The literature-based methodology was employed in this paper. The discussion is divided into two sections; the first part discusses the status and identity of nonnative English-speaking teachers and the second part delineates the actions for self-confidence of nonnative teachers of English as an international language. To conclude, Teaching English must emphasize on the teacher’s quality of the English teaching competence rather than the irrelevant nonnative identity. Furthermore, actions need to be executed by Nonnative English-speaking teachers (NNESTs) to enhance their performance in English language teaching in order to increase their self-confidence of their status in ELT and to be able to internationally compete.